2006
DOI: 10.1200/jco.2006.24.18_suppl.3003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates associated with a phase II study of temsirolimus (CCI-779) in patients with metastatic or recurrent endometrial cancer—NCIC IND 160

Abstract: 3003 Background: PTEN is a tumor suppressor gene and mutations in PTEN causing loss of protein expression/function may play a significant role in the pathogenesis of EC. Loss of PTEN protein expression has been reported in 26–80% of EC and leads to deregulated PI3K/Akt/mTOR signalling which may give neoplastic cells a survival advantage by enhancing angiogenesis, protein translation and cell cycle progression. Inhibition of mTOR, a protein kinase downstream of the PI3K/Akt pathway and target of rapamycins, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The National Cancer Institute of Canada reported a preliminary response rate of 26% in chemotherapynaive endometrial cancer patients treated with temsirolimus, an mTOR inhibitor. 60 Response in this group of patients was not correlated to PTEN status as evaluated by immunohistochemistry. Preliminary studies of other mTOR inhibitors, everolimus and AP2357, have shown clinical responses mainly in the form of stable disease (8 of 15 and 7 of 19 women, respectively).…”
Section: Targeted Therapymentioning
confidence: 74%
“…The National Cancer Institute of Canada reported a preliminary response rate of 26% in chemotherapynaive endometrial cancer patients treated with temsirolimus, an mTOR inhibitor. 60 Response in this group of patients was not correlated to PTEN status as evaluated by immunohistochemistry. Preliminary studies of other mTOR inhibitors, everolimus and AP2357, have shown clinical responses mainly in the form of stable disease (8 of 15 and 7 of 19 women, respectively).…”
Section: Targeted Therapymentioning
confidence: 74%
“…Oza et al from the National Cancer Institute of Canada evaluated CCI‐779 (temsirolimus; Wyeth Pharmaceuticals, Madison, NJ) in patients with untreated (as first‐line treatment) metastatic or recurrent endometrial cancer 10. Temsirolimus is an mTOR inhibitor available in an intravenous formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Temsirolimus, an intravenous mTORC1 inhibitor (25 mg weekly), showed efficacy as monotherapy for advanced and recurrent EC with ORRs of 22-25%. [187][188][189] Ridaforolimus is another intravenous mTORC1 inhibitor, administrated at a dose of 12.5 mg daily for 5 consecutive days every 2 weeks, showing a modest therapeutic efficacy as a single agent. 190 A phase II trial studied the efficacy and tolerability of ridaforolimus in recurrent and advanced EC with an ORR of 8.8% and a SD of 52.9%.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%